2021
DOI: 10.1016/j.chest.2021.07.1687
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sepsis on Outcomes of Hospitalizations Due to Copd

Abstract: PURPOSE: Chronic Obstructive Pulmonary Disease (COPD) is currently the fourth leading cause of death worldwide and its prevalence is expected to rise further. Sepsis is a life-threatening condition defined by organ dysfunction caused by a dysregulated host response to infection. Patients with COPD have been reported to be at a higher risk of developing sepsis due to the use of corticosteroids, underlying comorbidities, and possibly impaired barrier function. Hence in our study, we used the nationally represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…Concordant with other previous studies [ 19 22 ], our results confirmed that pre-intubation lactate level was associated with mortality of septic patients regardless of intubation status and induction agents used for RSI. Conversely, although chronic lung disease and respiratory infection have been identified as predictors of poor outcomes in previous studies [ 23 , 24 ], our study proved otherwise. Both factors could have been associated with lower mortality because patients with pathologies involving the respiratory system were possibly intubated earlier when their degree of sepsis severity was not as high compared to patients with infection at other sites.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Concordant with other previous studies [ 19 22 ], our results confirmed that pre-intubation lactate level was associated with mortality of septic patients regardless of intubation status and induction agents used for RSI. Conversely, although chronic lung disease and respiratory infection have been identified as predictors of poor outcomes in previous studies [ 23 , 24 ], our study proved otherwise. Both factors could have been associated with lower mortality because patients with pathologies involving the respiratory system were possibly intubated earlier when their degree of sepsis severity was not as high compared to patients with infection at other sites.…”
Section: Discussioncontrasting
confidence: 73%
“…Further studies, preferably prospectively conducted, with enough outcome events and complete data on important and potential associated factors should be conducted. Lastly, it is even more important to note that it is still unclear whether these independent factors are specific to patients receiving etomidate since many of these factors have also been identified as predictors of adverse outcomes in general septic patients receiving any induction agents [ 21 , 23 , 24 , 33 ]. Ideally, further studies comparing etomidate to other induction agents in septic patients should be performed.…”
Section: Limitationsmentioning
confidence: 99%